Daily Physical Activity Assessed by a Triaxial Accelerometer Is Beneficially Associated with Waist Circumference, Serum Triglycerides, and Insulin Resistance in Japanese Patients with Prediabetes or Untreated Early Type 2 Diabetes - Hidetaka Hamasaki; Mitsuhiko Noda; Sumie Moriyama; Reo Yoshikawa; Hisayuki Katsuyama; Akahito Sako; Shuichi Mishima; Masafumi Kakei; Osamu Ezaki; Hidekatsu Yanai (Journal of Diabetes Research)
Aim. To investigate the association between daily physical activity and metabolic risk factors in Japanese adults with prediabetes or untreated early type 2 diabetes (T2D). Methods. Daily physical activity level was measured using a triaxial accelerometer. We assessed correlations between physical activity level and waist circumference, blood pressure, fasting levels of plasma glucose, serum triglycerides, and insulin and homeostasis model assessment-insulin resistance (HOMA-IR). Results. A total of 80 patients were studied. After adjustment for age and body mass index, in all subjects, physical activity level was negatively associated with waist circumference (β=-0.124, P=0.018) and fasting serum triglycerides (β=-0.239, P=0.035), insulin (β=-0.224, P=0.022). In men, physical activity level was negatively associated with systolic blood pressure (β=-0.351, P=0.044), fasting plasma glucose (β=-0.369, P=0.025) and insulin (β=-0.362, P=0.012), and HOMA-IR (β=-0.371, P=0.011). No significant associations were found between physical activity level and metabolic risk factors in women. Conclusion. Objectively measured daily physical activity is beneficially associated with waist circumference, serum triglycerides, and insulin resistance in individuals with prediabetes or untreated early T2D. (This trial is registered with UMIN000015774.)